2005
DOI: 10.1242/jcs.02342
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted analysis of filopod formation and the role of myosin II heavy chain phosphorylation inDictyostelium

Abstract: To investigate the role played by filopodia in the motility and chemotaxis of amoeboid cells, a computer-assisted 3D reconstruction and motion analysis system, DIAS 4.0, has been developed. Reconstruction at short time intervals of Dictyostelium amoebae migrating in buffer or in response to chemotactic signals, revealed that the great majority of filopodia form on pseudopodia, not on the cell body; that filopodia on the cell body originate primarily on pseudopodia and relocate; and that filopodia on the uropod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 59 publications
4
51
0
Order By: Relevance
“…4C). By tracking the position of the uropod of each cell, which possessed a visible cluster of tail fibers under the microscopic conditions employed (Heid et al, 2005) (not shown here), it was clear that the uropod retained its integrity and followed the direction of the lateral pseudopod that extended in the correct direction, a turn similar to that described for cells turning in the absence of attractant . Five additional cells experiencing gradient reversal exhibited similar pseudopod dynamics to the one represented in Fig.…”
Section: Reversing the Gradient During Ca 2+ Chemotaxissupporting
confidence: 54%
“…4C). By tracking the position of the uropod of each cell, which possessed a visible cluster of tail fibers under the microscopic conditions employed (Heid et al, 2005) (not shown here), it was clear that the uropod retained its integrity and followed the direction of the lateral pseudopod that extended in the correct direction, a turn similar to that described for cells turning in the absence of attractant . Five additional cells experiencing gradient reversal exhibited similar pseudopod dynamics to the one represented in Fig.…”
Section: Reversing the Gradient During Ca 2+ Chemotaxissupporting
confidence: 54%
“…However, Wessels et al found that pten -cells are defective in myosin II assembly at the cell cortex in response to chemoattractant, providing insight into the possible mechanism underlying the lack of repression of lateral pseudopodia in these cells (Wessels et al, 2007). Indeed, myosin II normally localizes to the sides and rear of chemotactic neutrophils and Dictyostelium cells, where it prevents the formation of lateral pseudopodia and promotes cell body contraction and posterior retraction (Heid et al, 2005;Heid et al, 2004;Stites et al, 1998;Uchida et al, 2003;Wessels et al, 1988;Xu et al, 2003). Given its sequence similarity to the actin-binding protein tensin, Wessels et al further suggest that PTEN could directly interact with and modulate the F-actin-myosin cytoskeleton, implying that PTEN could play a role in cytoskeleton regulation that is independent of its PtdIns(3,4,5)P 3 phosphatase activity.…”
Section: Chemotaxis In the Absence Of Pi3k And/or Ptenmentioning
confidence: 99%
“…The assembly of actin-myosin filaments is suggested to stabilize the actin cytoskeleton and consequently enhance cortical rigidity, as well as to provide the motor activity necessary for efficient cell migration, through the ATP-driven translocation of actin filaments [124]. Myosin II localizes to the sides and rear of chemotactic neutrophils and Dictyostelium cells, where it prevents the formation of lateral pseudopodia and promotes cell-body contraction and posterior retraction [50,[125][126][127][128][129]. Despite its conserved role, myosin II appears to be differently regulated in mammalian and Dictyostelium cells [123,124,130].…”
Section: Regulation Of Actin-myosin Assemblymentioning
confidence: 99%